2020
DOI: 10.1101/2020.06.15.152868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary transcriptomics implicatesHAND2in the origins of implantation and regulation of gestation length

Abstract: The developmental origins and evolutionary histories of cell types, tissues and organ systems contribute to the ways in which their dysfunction leads to disease. In mammals for example, the nature and extent of maternal-fetal interactions, how those interactions develop, and their evolutionary history likely influence diseases of pregnancy such as infertility and preterm birth.Here we show genes that evolved to be expressed at the maternal-fetal interface in Eutherian (Placental) mammals play essential roles i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 175 publications
0
6
0
Order By: Relevance
“…Each of these subpopulations expressed marker genes identified previously by scRNA-seq reconstruction of the decidual pathway in standard primary EnSC cultures (Lucas et al, 2020). Pre-decidual cells in SS3 express HAND2, a key decidual transcription factor (Marinic et al, 2021), as well as previously identified genes encoding secreted factors, including VEGFA (vascular endothelial growth factor A), CRISPLD2 (a progesterone-dependent anti-inflammatory response gene coding cysteine rich secretory protein LCCL domain containing 2), IL15 (interleukin 15) and TIMP3 (TIMP metallopeptidase inhibitor 3) (Lucas et al, 2020). Novel candidate pre-decidual genes were also identified, such as DDIT4 (DNA damage inducible transcript 4), encoding a stress response protein intimately involved in autophagy, stemness and antioxidative defences (Ho et al, 2020, Miller et al, 2020.…”
Section: Cellular Complexity Of Decidualizing Assembloids Mimics Midluteal Endometriummentioning
confidence: 85%
“…Each of these subpopulations expressed marker genes identified previously by scRNA-seq reconstruction of the decidual pathway in standard primary EnSC cultures (Lucas et al, 2020). Pre-decidual cells in SS3 express HAND2, a key decidual transcription factor (Marinic et al, 2021), as well as previously identified genes encoding secreted factors, including VEGFA (vascular endothelial growth factor A), CRISPLD2 (a progesterone-dependent anti-inflammatory response gene coding cysteine rich secretory protein LCCL domain containing 2), IL15 (interleukin 15) and TIMP3 (TIMP metallopeptidase inhibitor 3) (Lucas et al, 2020). Novel candidate pre-decidual genes were also identified, such as DDIT4 (DNA damage inducible transcript 4), encoding a stress response protein intimately involved in autophagy, stemness and antioxidative defences (Ho et al, 2020, Miller et al, 2020.…”
Section: Cellular Complexity Of Decidualizing Assembloids Mimics Midluteal Endometriummentioning
confidence: 85%
“…Increased COUP-TFII expression by PGR-IHH signaling not only results in increased stromal PGR levels but also the levels of stromal heart and neural crest derivatives expressed transcript 2 ( Hand2 ) ( Li et al, 2011 ; Marinic et al, 2021 ; Figure 2A ), which is a basic helix-loop-helix transcription factor. To date, studies have not established whether the COUP-TFII transcription factor directly or indirectly (i.e., via stromal PGR) increases stromal Hand2 levels; however, HAND2 suppresses stromal fibroblast growth factor ( Fgf ) family members ( Fgf −1, −2, −9, and −18) in the endometrium ( Li et al, 2011 ; Figure 2A ).…”
Section: Endometrial Molecular Mediators Of the Progesterone Receptormentioning
confidence: 99%
“…Each of these subpopulations expressed marker genes identified previously by scRNA-seq reconstruction of the decidual pathway in standard primary EnSC cultures (Lucas et al, 2020). Pre-decidual cells in SS3 express HAND2 , a key decidual transcription factor (Marinic et al, 2021), as well as previously identified genes encoding secreted factors, including VEGFA (vascular endothelial growth factor A), CRISPLD2 (a progesterone-dependent anti-inflammatory response gene coding cysteine rich secretory protein LCCL domain containing 2) , IL15 (interleukin 15) and TIMP3 (TIMP metallopeptidase inhibitor 3) (Lucas et al, 2020). Novel pre-decidual genes were also identified, such as DDIT4 (DNA damage inducible transcript 4), encoding a stress response protein intimately involved in autophagy, stemness and antioxidative defences (Ho et al, 2020, Miller et al, 2020).…”
Section: Resultsmentioning
confidence: 67%